Improving Functional Characteristics of Wool and Some Synthetic Fibres - Allam, O. G. (Scientific Research, 2011)
The present article reviews recent developments in different treatments that confer functional characteristics on wool and some synthetic fibers such as acrylic, polyamide and polyester of these functionalities mention is made of shrinkage-resistance, felt proofing, ant pilling, antimicrobial, surface properties (hydrophilic, soil -resistance, water and oil-repellency), self-cleaning, anti odor and flame retardant. The article also illustrates nanotechnology applications to improve and / or to induce some of these properties. Improvement of these properties can give the fibres an important position between the textile fibres which make them more convenient in different uses.
Keywords: Functional; Wool; Synthetic Fibres